Thermal spray coating and thermal spray remanufacturing method for metal mold

By using thermal spray coatings containing cermet powder and a variety of oxides, a coating with good wear resistance is formed, which solves the problem that the prior art cannot fully extend the service life of the metal mold and achieves efficient maintenance results.

CN119753553APending Publication Date: 2025-04-04XIKE (YANCHENG) SURFACE COATING TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510050957.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing thermal spray remanufacturing process cannot fully extend the service life of metal molds that frequently suffer from high-strength wear, resulting in high later maintenance costs.

Method used

A thermal spray coating is used to form a coating through a thermal spraying process to improve the wear resistance and spreadability of the coating.

Benefits of technology

It achieves a good repair effect on the worn metal mold. The repaired coating can withstand high-strength friction for a long time, fully extending the service life of the metal mold and effectively reducing the later maintenance cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239935370000061
    Figure BDA0005239935370000061
  • Figure BDA0005239935370000071
    Figure BDA0005239935370000071
Patent Text Reader

Abstract

The present application relates to the field of surface processing technology, and specifically discloses a thermal spray coating and a thermal spray remanufacturing method for a metal mold. The thermal spray coating includes the following components in parts by weight: 70-75 parts of metal ceramic powder, 8-10 parts of aluminum oxide, 10-12 parts of zirconium oxide, 4-8 parts of cerium oxide, 10-15 parts of mullite andalusite, 3-6 parts of garnet, 4-6 parts of nano-silicon dioxide, 4-7 parts of modified whiskers, and 12-15 parts of binder; the modified whiskers are potassium hexatitanate whiskers coated with aluminum oxide on the surface. The thermal spray coating of the present application can produce a good repair effect on the worn metal mold, and the coating produced after the repair can withstand high-intensity friction for a long time, thereby fully extending the service life of the metal mold and effectively reducing the later maintenance cost of the metal mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of surface processing technology, and more specifically, to a thermal spray coating and a thermal spray remanufacturing method for a metal mold. Background Art

[0002] With the rapid development of modern industry, the mold industry, as a basic industry of industrial production, has received more and more attention. At present, diversification, high precision, high performance, long life and low cost have become the general development goals of the modern mold industry. Metal molds are the most common type of molds. Due to their large number and frequent use, the amount of scrapped metal molds is also very large. For metal molds that are close to being scrapped, in addition to smelting and recycling them, their service life can also be extended through remanufacturing technology. This has become a hot research topic in the mold industry.

[0003] Remanufacturing engineering is a general term for a series of technical measures or engineering activities to repair and transform waste products, guided by the theory of the entire life cycle of equipment, with the goal of achieving a leapfrog improvement in the performance of waste products, with high quality, high efficiency, energy saving, material saving, and environmental protection as the criteria, and advanced technology and industrialized production as the means. The principle of the thermal spray remanufacturing process is to heat the linear or powdered material to a molten or semi-molten state through a heat source such as flame, arc, plasma arc or laser, and atomize it through the blowing action of the airflow and spray it onto the surface of the substrate at high speed to form a coating. The thermal spray remanufacturing process can fill the worn parts on the surface of the metal mold, which helps to extend the service life of the metal mold.

[0004] Regarding the above-mentioned related technologies, the inventors believe that although the coating formed by the thermal spraying remanufacturing process can fill the worn parts on the surface of the metal mold, for some metal molds that are frequently subjected to high-intensity wear, the thermal spraying remanufacturing process currently on the market still cannot fully extend the service life of the metal mold, resulting in high subsequent maintenance costs for the metal mold. Summary of the invention

[0005] In the related art, for some metal molds that are frequently worn, the thermal spraying remanufacturing process currently available on the market still cannot fully extend the service life of the metal molds, resulting in high maintenance costs for the metal molds. In order to improve this defect, the present application provides a thermal spraying coating and a thermal spraying remanufacturing method for a metal mold.

[0006] In the first aspect, the present application provides a thermal spray coating, which adopts the following technical solution: A thermal spray coating comprises the following components in parts by weight: 70-75 parts of metal ceramic powder, 8-10 parts of aluminum oxide, 10-12 parts of zirconium oxide, 4-8 parts of cerium oxide, 10-15 parts of mullite andalusite, 3-6 parts of garnet, 4-6 parts of nano silicon dioxide, 4-7 parts of modified whiskers, and 12-15 parts of a binder; the modified whiskers are potassium hexatitanate whiskers with aluminum oxide coated on the surface.

[0007] By adopting the above technical scheme, the present application uses metal ceramic powder as the base material, and adds oxides such as aluminum oxide, zirconium oxide, cerium oxide, and nano-silicon dioxide, wherein aluminum oxide and nano-silicon dioxide can react under the high temperature conditions of the thermal spraying process to produce mullite with good wear resistance and dense structure; zirconium oxide and cerium oxide can synergistically improve the spreadability of the coating during spraying, and make the coating more uniform and dense through the synergistic effect with mullite. Mullitized andalusite is a mineral that uses andalusite as raw material and is partially converted into mullite after heat treatment. It can increase the total amount of mullite in the coating, and has a relatively ideal particle size distribution, and has good adaptability to the thermal spraying process. After compounding, mullitized andalusite can synergistically improve the wear resistance of the coating with metal ceramic powder, garnet, and mullite formed during the thermal spraying process. The aluminum oxide on the surface of the modified whiskers can react with nano-silicon dioxide under the high temperature conditions of the thermal spraying process to produce a mullite coating. The mullite coating can achieve a good combination of the modified whiskers and other components in the coating, reduce the pores in the coating, and can resist wear together with the potassium hexatitanate whiskers inside, which can effectively improve the wear resistance of the coating. Through the combination of the above components, the thermal spray coating of the present application can produce a good repair effect on the worn metal mold, and the coating produced after the repair can withstand high-intensity friction for a long time, thereby fully extending the service life of the metal mold and effectively reducing the later maintenance cost of the metal mold.

[0008] Preferably, the mullite andalusite is prepared according to the following method: The andalusite is crushed to obtain andalusite powder, and the andalusite powder is preheated to obtain primary mullite powder. The primary mullite powder is mixed with an auxiliary agent and then heated for a second time to obtain mullite andalusite; the auxiliary agent includes aluminum fluoride.

[0009] By adopting the above technical scheme, the present application uses andalusite as a raw material to prepare andalusite powder, and then preheats the andalusite powder itself to undergo a mullite reaction. Subsequently, in the secondary heating process with the participation of an auxiliary agent, aluminum fluoride reacts with silicon dioxide in the andalusite powder to produce fluorotopaz, which then decomposes to produce silicon fluoride vapor, and aluminum oxide in the andalusite powder reacts with silicon fluoride vapor to form aluminum fluoride, thereby achieving a cycle. In this cycle, aluminum fluoride is theoretically not lost, so it can play a catalytic role and promote the mullite reaction. The mullite degree of andalusite is improved; in addition, aluminum fluoride mixed in mullitized andalusite can also promote the formation of mullite during thermal spraying, so that the mullitized andalusite prepared in the above manner helps to improve the wear resistance of the coating.

[0010] Preferably, the auxiliary agent comprises nano-aluminum oxide.

[0011] By adopting the above technical solution, the addition of nano-alumina can provide additional reactants for the mullite reaction, promote the mullite reaction of andalusite, and help improve the wear resistance of the coating.

[0012] Preferably, the weight of the nano-alumina is 20-25% of the weight of the primary mullite powder.

[0013] By adopting the above technical solution, the present application optimizes the dosage of nano-alumina, promotes the mullite reaction of andalusite, and helps to improve the wear resistance of the coating.

[0014] Preferably, the auxiliary agent further comprises yttrium oxide.

[0015] By adopting the above technical solution, the addition of yttrium oxide can increase the diffusion rate of silicon and aluminum, promote the formation of mullite phase, and the yttrium ions can occupy the position of aluminum ions in the alumina octahedral structure, so that the excess silicon dioxide forms a viscous liquid phase, thereby filling the pores, which can increase the density of the mullite phase and help improve the wear resistance of the coating.

[0016] Preferably, the amount of yttrium oxide used is 3.5-5.5% of the weight of the primary mullite powder.

[0017] By adopting the above technical solution, the present application optimizes the dosage range of yttrium oxide, which helps to improve the wear resistance of the coating.

[0018] Preferably, the auxiliary agent also includes nano lanthanum oxide.

[0019] By adopting the above technical solution, the lanthanum ions in the nano-lanthanum oxide can occupy the position of the aluminum ions in the aluminum oxide octahedral structure, so that the excess silicon dioxide forms a viscous liquid phase, thereby filling the pores and increasing the density of the mullite phase. At the same time, the nano-lanthanum oxide can also cause the large-grained mullite grains to break into short columns, thereby forming an interwoven network structure, which is conducive to the filling of the silicon dioxide liquid phase. Therefore, under the action of the silicon dioxide liquid phase, the density of the mullite phase can be fully improved, which helps to improve the wear resistance of the coating.

[0020] Preferably, the dosage of the nano-lanthanum oxide is 5-7% of the weight of the primary mullite powder.

[0021] By adopting the above technical solution, the present application optimizes the dosage range of nano-lanthanum oxide, which helps to improve the wear resistance of the coating.

[0022] Preferably, the modified whisker is prepared according to the following method: (1) adding sodium silicate to water and dissolving it to obtain a sodium silicate solution, which is set aside; adding potassium hexatitanate whiskers to water and mixing to obtain a whisker slurry, which is set aside; (2) adding sodium silicate solution to the whisker slurry, adjusting the pH value, filtering, washing and drying after heat preservation and aging to obtain modified whiskers.

[0023] By adopting the above technical solution, the present application first prepares a sodium silicate solution and a whisker slurry respectively, and then converts the sodium silicate into silicic acid by acidification after mixing the two. After filtering, washing and drying, the silicic acid attached to the surface of the potassium hexatitanate whisker is completely dehydrated to obtain the modified whisker.

[0024] In a second aspect, the present application provides a thermal spraying remanufacturing method for a metal mold, which adopts the following technical solution.

[0025] A thermal spraying remanufacturing method for a metal mold comprises the following steps: (1) mixing metal ceramic powder, aluminum oxide, zirconium oxide, cerium oxide, mullite andalusite, garnet, mullite fiber, nano silicon dioxide, modified whisker, and a binder to obtain any of the above thermal spray coatings for standby use; (2) The surface of the metal mold is cleaned and roughened, and then the surface of the metal mold is preheated. The workpiece is fixed on the thermal spraying equipment, the spraying parameters are set, and then the thermal spraying material of step (1) is used to spray the surface of the metal mold, thereby realizing the thermal spraying remanufacturing of the metal mold.

[0026] By adopting the above technical solution, the present application first prepares the thermal spray coating, and then uses the thermal spray coating to spray the metal mold, thereby realizing the thermal spray remanufacturing of the metal mold.

[0027] In summary, this application has the following beneficial effects: 1. The thermal spray coating of the present application can produce a good repair effect on the worn metal mold, and the coating produced after the repair can withstand high-intensity friction for a long time, thereby fully extending the service life of the metal mold and effectively reducing the later maintenance cost of the metal mold.

[0028] 2. In the present application, aluminum fluoride, nano-alumina, yttrium oxide, and nano-lanthanum oxide are preferably used as additives. With the participation of the above additives, mullite andalusite with high density and good wear resistance is prepared, which can effectively improve the wear resistance of the coating. DETAILED DESCRIPTION

[0029] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0030] Preparation Example of Mullite andalusite The following is an explanation using Preparation Example 1.

[0031] Preparation Example 1 In this preparation example, aluminum fluoride trihydrate is selected as the auxiliary agent, and the weight of aluminum fluoride in aluminum fluoride trihydrate is 10% of the total weight of the primary mullite powder; the aluminum oxide content of andalusite is 52.7wt%, and the silicon dioxide content is 42.2wt%.

[0032] In this preparation example, mullite andalusite is prepared according to the following method: The andalusite was crushed to obtain andalusite powder with an average particle size of 15 μm, and the andalusite powder was preheated at 1480° C. for 2 hours to obtain a primary mullite powder. The primary mullite powder was mixed with an additive, and then secondary heated at 1480° C. for 3 hours to obtain mullite andalusite.

[0033] Preparation Example 2 The difference between this preparation example and preparation example 1 is that the auxiliary agent further comprises nano-alumina, and the weight of the nano-alumina is 15% of the weight of the primary mullite powder.

[0034] Preparation Example 3 The difference between this preparation example and preparation example 2 is that the weight of nano-alumina is 20% of the weight of the primary mullite powder.

[0035] Preparation Example 4 The difference between this preparation example and preparation example 2 is that the weight of nano-alumina is 22.5% of the weight of the primary mullite powder.

[0036] Preparation Example 5 The difference between this preparation example and preparation example 2 is that the weight of nano-alumina is 25% of the weight of the primary mullite powder.

[0037] Preparation Example 6 The difference between this preparation example and preparation example 5 is that the auxiliary agent further includes yttrium oxide, and the amount of yttrium oxide used is 2.5% of the weight of the primary mullite powder.

[0038] Preparation Example 7 The difference between this preparation example and preparation example 5 is that the auxiliary agent further includes yttrium oxide, and the amount of yttrium oxide used is 3.5% of the weight of the primary mullite powder.

[0039] Preparation Example 8 The difference between this preparation example and preparation example 5 is that the auxiliary agent further includes yttrium oxide, and the amount of yttrium oxide used is 4.5% of the weight of the primary mullite powder.

[0040] Preparation Example 9 The difference between this preparation example and preparation example 5 is that the auxiliary agent further includes yttrium oxide, and the amount of yttrium oxide used is 5.5% of the weight of the primary mullite powder.

[0041] Preparation Example 10 The difference between this preparation example and preparation example 9 is that the auxiliary agent further includes nano-lanthanum oxide, and the amount of nano-lanthanum oxide used is 3% of the weight of the primary mullite powder.

[0042] Preparation Example 11 The difference between this preparation example and preparation example 10 is that the amount of nano-lanthanum oxide used is 5% of the weight of the primary mullite powder.

[0043] Preparation Example 12 The difference between this preparation example and preparation example 10 is that the amount of nano-lanthanum oxide used is 6% of the weight of the primary mullite powder.

[0044] Preparation Example 13 The difference between this preparation example and preparation example 10 is that the amount of nano-lanthanum oxide used is 7% of the weight of the primary mullite powder.

[0045] Preparation example of modified whiskers The following is an explanation using Preparation Example 14 as an example.

[0046] Preparation Example 14 In this preparation example, the specification of the potassium hexatitanate whisker is 100 mesh, the amount of silicon dioxide coating on the surface of the potassium hexatitanate whisker is 8 wt %, and the sodium silicate is weighed according to this amount.

[0047] In this preparation example, the modified whiskers were prepared according to the following method: (1) adding sodium silicate to water and dissolving it to obtain a 5 wt % sodium silicate solution for later use; adding potassium hexatitanate whiskers to water and mixing to obtain a whisker slurry with a whisker content of 15 wt % for later use; (2) adding the sodium silicate solution to the whisker slurry under a water bath heating condition of 75° C., adjusting the pH to 11.5, and aging at 75° C. for 5 h, filtering, washing and drying to obtain modified whiskers. Example

[0048] Examples 1-5 The following description is given by taking Example 1 as an example.

[0049] Example 1 In this embodiment, the material of the metal ceramic powder is NiCr-Cr3C2, the mullite andalusite is prepared according to the method of Preparation Example 1, and the modified whisker is prepared according to the method of Preparation Example 14. The average particle size of the metal ceramic powder, alumina, zirconium oxide (ZrO2), and cerium oxide (CeO2) is 12 μm, the average particle size of garnet is 5.8 μm, the average particle size of nano-silicon dioxide is 50 nm, and aluminum dihydrogen phosphate is selected as the binder.

[0050] The present embodiment provides a thermal spray coating, comprising the following components: 70 g of metal ceramic powder, 8 g of aluminum oxide, 10 g of zirconium oxide, 4 g of cerium oxide, 10 g of mullite, 3 g of garnet, 4 g of nano-silicon dioxide, 4 g of modified whiskers, and 12 g of a binder.

[0051] This embodiment provides a thermal spraying remanufacturing method for a metal mold, comprising the following steps: (1) mixing metal ceramic powder, aluminum oxide, zirconium oxide, cerium oxide, mullite andalusite, garnet, nano silicon dioxide, modified whiskers, and a binder to obtain a thermal spray coating for standby use; (2) The surface of the metal mold is cleaned and roughened, and then the surface of the metal mold is preheated. The workpiece is fixed on the thermal spraying equipment, and the spraying parameters are set to spray power 35 kW, spray distance 200 mm, and coating thickness 300 μm. Then, the thermal spraying material of step (1) is used to spray the surface of the metal mold to achieve thermal spraying remanufacturing of the metal mold.

[0052] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the thermal spray coatings.

[0053] Table 1 Raw material ratio of thermal spray coating As shown in Table 2, the difference between Examples 5-17 is that the preparation examples of mullite andalusite are different.

[0054] Table 2 Preparation example of mullite andalusite sample Preparation Example Example 5 Preparation Example 1 Example 6 Preparation Example 2 Example 7 Preparation Example 3 Example 8 Preparation Example 4 Example 9 Preparation Example 5 Example 10 Preparation Example 6 Embodiment 11 Preparation Example 7 Example 12 Preparation Example 8 Example 13 Preparation Example 9 Embodiment 14 Preparation Example 10 Embodiment 15 Preparation Example 11 Example 16 Preparation Example 12 Embodiment 17 Preparation Example 13 Comparative Example Comparative Example 1 The difference between this comparative example and Example 1 is that the components of the thermal spray coating only include metal ceramic powder.

[0055] Comparative Example 2 This comparative example is different from Example 1 in that the composition of the thermal spray coating does not include zirconium oxide.

[0056] Comparative Example 3 This comparative example is different from Example 1 in that the composition of the thermal spray coating does not include cerium oxide.

[0057] Comparative Example 4 This comparative example is different from Example 1 in that the composition of the thermal spray coating does not include aluminum oxide.

[0058] Comparative Example 5 The difference between this comparative example and Example 1 is that the components of the thermal spray coating do not include nano-silicon dioxide.

[0059] Comparative Example 6 The difference between this comparative example and Example 1 is that the mullite in the thermal spray coating component is replaced with andalusite.

[0060] Comparative Example 7 The difference between this comparative example and Example 1 is that the modified whiskers in the thermal spray coating component are replaced with potassium hexatitanate whiskers.

[0061] Performance test method The sample matrix material is 45 steel, which is processed into a sample block with a size of 9×10×12mm. After degreasing, washing and drying, it is used as a sample. According to the methods of each embodiment and comparative example, thermal spray coating is used to perform thermal spraying and remanufacturing on the surface of the sample, and then the wear resistance of the sample is tested using an MM200 wear tester. The rotation speed is 0.4m / s, the load is 350N, and the wear time is 40min. The material of the friction ring is GCr15 steel, and heat treatment is performed before the wear experiment to make the average hardness of the friction ring reach 61HRC. The wear mass loss is used to characterize the wear resistance of the coating. Taking the mass loss of comparative example 1 as the benchmark, the ratio between the mass loss of each embodiment and comparative example and the mass loss of comparative example 1 is calculated, and the ratio is recorded as the relative mass loss. The results are shown in Table 2.

[0062] Table 2 Relative mass loss sample Relative mass loss / % sample Relative mass loss / % Example 1 64.9 Example 13 55.4 Example 2 64.4 Embodiment 14 54.8 Example 3 64.2 Embodiment 15 54.5 Example 4 64.0 Example 16 54.2 Example 5 63.7 Embodiment 17 53.6 Example 6 61.4 Comparative Example 1 100.0 Example 7 60.7 Comparative Example 2 77.4 Example 8 60.1 Comparative Example 3 73.1 Example 9 59.3 Comparative Example 4 80.3 Example 10 57.5 Comparative Example 5 84.6 Embodiment 11 57.1 Comparative Example 6 90.2 Example 12 56.3 Comparative Example 7 93.5 Combining Examples 1-5 and Comparative Example 1 and Table 2, it can be seen that the relative loss mass measured in Examples 1-5 is lower than that in Comparative Example 1. This is because the aluminum oxide and nano-silicon dioxide in Example 1 react at high temperature to produce mullite, which synergistically improves the wear resistance of the coating with mullitized andalusite, metal ceramic powder, garnet and modified whiskers. In addition, zirconium oxide and cerium oxide synergistically improve the spreadability of the coating during spraying, and the mullite coating on the surface of the modified whisker reduces the pores in the coating, and can cooperate with the potassium hexatitanate whiskers inside to achieve wear resistance, so the coating loss on the surface of the samples of Examples 1-5 is less.

[0063] It can be seen from Example 1 and Comparative Examples 2-3 and Table 2 that in the absence of either zirconium oxide or cerium oxide, since the spreadability of the coating during spraying is not effectively improved, the relative loss mass measured in Comparative Examples 2-3 is higher, indicating that the coating has a higher loss.

[0064] Combining Example 1 and Comparative Examples 4-5 and Table 2, it can be seen that when any one of alumina and nano-silica is missing, the formation of mullite is affected, so the synergistic anti-wear effect of the components is not good, resulting in a higher relative loss mass measured in Comparative Examples 4-5.

[0065] Combining Example 1 and Comparative Examples 6-7 and Table 2, it can be seen that when the andalusite is not modified by mullite or the surface of the potassium hexatitanate whisker lacks a coating layer, the synergistic anti-wear effect between the components is not good, resulting in a higher relative loss mass measured in Comparative Examples 6-7.

[0066] Combining Example 5 with Examples 6-9 and Table 2, it can be seen that the relative loss mass measured in Examples 6-9 is lower, because the addition of nano-alumina can provide additional reactants for the mullite reaction, promote the mullite reaction of andalusite, and help improve the wear resistance of the coating. Moreover, when the weight of nano-alumina is 20-25% of the weight of the primary mullite powder, the improvement effect is better.

[0067] Combining Example 9, Example 10-13 and Table 2, it can be seen that the relative loss mass measured in Example 10-13 is relatively low. This is because the addition of yttrium oxide can increase the diffusion rate of silicon and aluminum, promote the formation of mullite phase, and yttrium ions can occupy the position of aluminum ions in the aluminum oxide octahedral structure, so that excess silicon dioxide forms a viscous liquid phase, thereby filling the pores, which can increase the density of the mullite phase and help improve the wear resistance of the coating. Moreover, when the amount of yttrium oxide is 3.5-5.5% of the weight of the primary mullite powder, this improvement effect is better.

[0068] It can be seen from Example 13, Example 14-17 and Table 2 that the relative loss mass measured in Example 14-17 is relatively low. This is because the lanthanum ions in the nano-lanthanum oxide can occupy the position of the aluminum ions in the aluminum oxide octahedral structure, so that the excess silicon dioxide forms a viscous liquid phase, thereby filling the pores and increasing the density of the mullite phase. At the same time, the nano-lanthanum oxide can also cause the large-grained mullite grains to break into short columns, thereby forming an interwoven network structure. This network structure can fully improve the density of the mullite phase through the cooperation with the silicon dioxide liquid phase, which helps to improve the wear resistance of the coating. Moreover, when the amount of nano-lanthanum oxide is 5-7% of the weight of the primary mullite powder, this improvement effect is better.

[0069] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A thermal spray coating, characterized in that: The invention comprises the following components in parts by weight: 70-75 parts of metal ceramic powder, 8-10 parts of aluminum oxide, 10-12 parts of zirconium oxide, 4-8 parts of cerium oxide, 10-15 parts of mullite andalusite, 3-6 parts of garnet, 4-6 parts of nano silicon dioxide, 4-7 parts of modified whiskers and 12-15 parts of a binder; the modified whiskers are potassium hexatitanate whiskers with aluminum oxide coated on the surface.

2. The thermal spray coating according to claim 1, characterized in that: The mullite andalusite is prepared according to the following method: The andalusite is crushed to obtain andalusite powder, and the andalusite powder is preheated to obtain primary mullite powder. The primary mullite powder is mixed with an auxiliary agent and then heated for a second time to obtain mullite andalusite; the auxiliary agent includes aluminum fluoride.

3. The thermal spray coating according to claim 2, characterized in that: The auxiliary agent includes nano alumina.

4. The thermal spray coating according to claim 3, characterized in that: The weight of the nano-alumina is 20-25% of the weight of the primary mullite powder.

5. The thermal spray coating according to claim 3, characterized in that: The auxiliary agent also includes yttrium oxide.

6. The thermal spray coating according to claim 5, characterized in that: The amount of yttrium oxide used is 3.5-5.5% of the weight of the primary mullite powder.

7. The thermal spray coating according to claim 5, characterized in that: The auxiliary agent also includes nano lanthanum oxide.

8. The thermal spray coating according to claim 7, characterized in that: The dosage of the nano-lanthanum oxide is 5-7% of the weight of the primary mullite powder.

9. The thermal spray coating according to claim 7, characterized in that: The modified whiskers are prepared according to the following method: (1) adding sodium silicate to water and dissolving it to obtain a sodium silicate solution, which is set aside; adding potassium hexatitanate whiskers to water and mixing to obtain a whisker slurry, which is set aside; (2) Adding sodium silicate solution to the whisker slurry and adjusting the pH value, filtering, washing and drying the slurry after heat preservation and aging to obtain modified whiskers.

10. A thermal spraying remanufacturing method for a metal mold, characterized in that: The following steps are involved: (1) Mixing metal ceramic powder, alumina, zirconium oxide, cerium oxide, mullite andalusite, garnet, nano-silicon dioxide, modified whiskers, and a binder to obtain the thermal spray coating according to any one of claims 1 to 9, and setting it aside; (2) The surface of the metal mold is cleaned and roughened, and then the surface of the metal mold is preheated. The workpiece is fixed on the thermal spraying equipment, the spraying parameters are set, and then the thermal spraying material of step (1) is used to spray the surface of the metal mold, thereby realizing the thermal spraying remanufacturing of the metal mold.